Conduct of doctor: court takes a serious view - Setia, Puneet; Shekhawat, Raghvendra Singh (International Surgery Journal, 2016)
The cases of alleged medical negligence are being reported increasingly day by day and already it has become a great problem for medical professionals. In this context the recent verdict passed by the supreme court of India in the case Dr. P.B. Desai vs. state of Maharashtra & ANR on 13-9-2013 needs special mention. The verdict states that the conduct of the doctor is paramount while discharging his duties as caregiver.